Rapid VR Prototyping for Academia and Industry: A Tutorial on Building Interactive Experiences with Godot and the XR Tools Framework - Nobrega, João Anisio Marinho da; Lima, Felipe Fausto de Azevedo; Melo, Marcos Arthur da Silva; Bessa, Gabriel Henrique Ferreira; Souza, Alyson Matheus de Carvalho (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
This paper outlines a 3-hour tutorial focused on rapid prototyping of Virtual Reality (VR) experiences using the Godot Engine in conjunction with the Godot XR Tools framework. The tutorial aims to equip participants from academic and industrial backgrounds with a modern, efficient workflow, shifting the focus from low-level boilerplate coding to high-level VR design concepts and rapid iteration. By leveraging the pre-built functionalities of Godot XR Tools for common VR mechanics such as locomotion and interaction, participants can achieve significant results within a short timeframe. This approach not only accelerates development but also aligns with real-world practices where leveraging libraries and specialized tools is standard. The manuscript details the rationale for this tool-centric methodology, presents the structured content of the tutorial, and discusses its pedagogical benefits and contributions to the VR development community, particularly in fostering accessible and scalable prototyping solutions.